2007
DOI: 10.1161/atvbaha.107.142117
|View full text |Cite
|
Sign up to set email alerts
|

Nox1 Mediates Basic Fibroblast Growth Factor-Induced Migration of Vascular Smooth Muscle Cells

Abstract: Objectives-Basic fibroblast growth factor (bFGF) stimulates vascular smooth muscle cell (SMC) migration. We determined whether bFGF increases SMC reactive oxygen-species (ROS) and studied the role of ROS for SMC migration. Methods and Results-bFGF rapidly increased rat SMC ROS formation and migration through pathways sensitive to inhibition of NADPH oxidases, PI3-kinase, protein kinase C, and Rac-1. SiRNA directed against the NADPH oxidase Nox4 impaired basal but not bFGF-induced ROS formation and did not affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 40 publications
9
108
0
4
Order By: Relevance
“…Many reports showed, by using pharmacological inhibition, that ROS produced through an NADPH oxidase-like complex affect cell migration (23,49). Recent molecular evidence for the involvement of Nox/Duox homologues in the control of cell migration has been reported for Nox2 in endothelial cells (45,54), Nox1 in vascular smooth muscle cells and colonic epithelial cells (38,40), Nox4 in myofibroblast and vascular smooth muscle cells (15,16,28), and Duox1 in airway epithelial cells (49). In a previous report, we showed that Nox1 controls colonic epithelial cell migration on Col-I by modulating ␣2 integrin membrane availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports showed, by using pharmacological inhibition, that ROS produced through an NADPH oxidase-like complex affect cell migration (23,49). Recent molecular evidence for the involvement of Nox/Duox homologues in the control of cell migration has been reported for Nox2 in endothelial cells (45,54), Nox1 in vascular smooth muscle cells and colonic epithelial cells (38,40), Nox4 in myofibroblast and vascular smooth muscle cells (15,16,28), and Duox1 in airway epithelial cells (49). In a previous report, we showed that Nox1 controls colonic epithelial cell migration on Col-I by modulating ␣2 integrin membrane availability.…”
Section: Discussionmentioning
confidence: 99%
“…Abrogation of Nox1-dependent ROS production by diphenyleneiodonium (DPI) or small interfering RNA restores RhoA activation and actin stress fiber formation (41). More recently, several groups have highlighted a key role of Nox1 in the control of growth factorinduced migration (16,38,40). Cancer cells probably undergo random migration during metastasis, but their migration can be directed by cytokine gradients and/or associated with ECM fibers (29,55).…”
mentioning
confidence: 99%
“…ROS mediated fibroblast migration by increasing phosphorylation of Cortactin (22). In addition, ROS mediated growth factor-induced migration of vascular smooth muscle cells (23).…”
Section: Ha Increases the Ros Level In Melanoma Cells And Cellmentioning
confidence: 97%
“…4,5,19,20 Nox1 upregulation has been postulated to promote vascular cell proliferation and migration during restenosis. 20 Schröder et al 21 reported recently that migration of vascular smooth muscle cells induced by fibroblast growth factor is mediated by Nox1. We reported that the vascular adventitia expresses the Nox2-based oxidase system, which is involved in the production of O 2 Ϫ by adventitial fibroblasts 22,23 and neointimal hyperplasia, 5,24 with the latter process being partially attributed to the migration of adventitial myofibroblasts.…”
mentioning
confidence: 99%